Low Temperature Magnetic Properties of Variably Oxidized Natural and Synthetic Siderite - Mark J. Dekkers; Wout Hanckmann; Simo Spassov; Thilo Behrends (Geochemistry, Geophysics, Geosystems, 2023)
Abstract Siderite (FeCO3) is an important ferrous iron carbonate in the geochemical cycling of iron, as it is a sink for iron under reducing conditions. However, its detection is not straightforward with classical analytical approaches because in natural samples it is often fine‐grained and/or occurs in low concentrations. In this study, we explore the analytical potential of low‐temperature magnetometry. Synthetic siderites with a limited amount of associated ferric iron of up to 5 mol% and some natural siderites were subjected to investigation. Maxima in the cooling curves in a 5 T magnetic field shows that the Néel temperature of siderite is at 37 K in agreement with literature data. Those maxima appear at a higher temperature in the synthetic siderites with associated/sorbed ferric iron; it is 45 K for the 5 mol% Fe3+ synthesis. With the increasing amount of ferric iron, the synthetic siderites show an increasingly prominent remanence tail beyond the nominal Néel temperature in field‐cooled (FC) and zero‐field‐cooled (ZFC) warming curves of the remanent magnetization acquired in 5 T at 5 K. Fine‐grained siderite alters in air on laboratory time scales which is manifested by more pronounced remanence tails up to higher temperatures. Siderite's presence is best diagnosed by evaluating a combination of FC warming curves and a FC/ZFC remanence ratio >3 at 5 K. Standard addition experiments of FC warming curves enable the determination of siderite down to 0.1 wt%.